FIRST FOSSIL RECORD OF ASPREDINIDAE: A NEW SPECIES FROM THE LATE MIOCENE OF NORTHEASTERN ARGENTINA - Bogan, Sergio; Agnolín, Federico L. (Zootaxa, 2024)
This study aims to describe a new fossil species of the extant aspredinid genus Bunocephalus. The new species is represented by a nearly complete skull and pectoral girdle coming from late Miocene Ituzaingó Formation beds of Paraná City, Entre Ríos Province, Argentina. The specimen constitutes the first fossil record for the genus and the family Aspredinidae. This finding demonstrates that large temporal and geographical gaps are still present in the fossil record of the South American continent, evidencing the lack of knowledge of the geographical and temporal distribution of many freshwater fish clades.